2016
DOI: 10.1007/s00125-016-3913-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional networks of murine diabetic peripheral neuropathy and nephropathy: common and distinct gene expression patterns

Abstract: Aims/hypothesis Diabetic peripheral neuropathy (DPN) and diabetic nephropathy (DN) are two common microvascular complications of type 1 and type 2 diabetes mellitus that are associated with a high degree of morbidity. In this study, using a variety of systems biology approaches, our aim was to identify common and distinct mechanisms underlying the pathogenesis of these two complications. Methods Our previously published transcriptomic datasets of peripheral nerve and kidney tissue, derived from murine models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 38 publications
5
35
0
Order By: Relevance
“…In 2017, it was estimated that 451 million people worldwide suffer from diabetes, including 30 million Americans [1,2], with type 2 diabetes (T2D) accounting for approximately 90% to 95% of the diagnosed cases. T2D is primarily characterized by hyperglycaemia, hyperlipidaemia, and insulin resistance [3]. Both subjects with type 1 (T1D) and T2D experience diabetes-related microvascular complications which have a negative impact on the quality of life and affect multiple tissues including the nerve (diabetic neuropathy), kidney (diabetic nephropathy) and eye (diabetic retinopathy) [4].…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, it was estimated that 451 million people worldwide suffer from diabetes, including 30 million Americans [1,2], with type 2 diabetes (T2D) accounting for approximately 90% to 95% of the diagnosed cases. T2D is primarily characterized by hyperglycaemia, hyperlipidaemia, and insulin resistance [3]. Both subjects with type 1 (T1D) and T2D experience diabetes-related microvascular complications which have a negative impact on the quality of life and affect multiple tissues including the nerve (diabetic neuropathy), kidney (diabetic nephropathy) and eye (diabetic retinopathy) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although the metabolic response of these tissues to diabetes has historically been thought to be similar and downstream of altered glucose metabolism (20), we recently found that glucose and fatty acid oxidation are tissue specific and dissimilar among the three diabetic end-organ target tissues of kidney, nerve, and retina (21). Transcriptomic analysis identified several pathways involved in lipid biosynthesis that were enriched in both the diabetic mouse kidney and nerve (21), although dysregulation of gene expression in the diabetic kidney and nerve was overall discordant (22,23). Transcriptomic data indicates altered lipid synthesis, but there is a lack of information on broader lipid changes derived from synthesis in these diabetic tissues and how any lipid changes relate to mRNA expression.…”
mentioning
confidence: 99%
“…As seen in Fig. 4B, at all the time points (24,48, and 72 h), HDAC1 and HDAC5 were increased with high-glucose stimulation (P , 0.05). Particularly at 72 h after high-glucose stimulation, HDAC1 and HDAC5 were respectively increased by 3.48 and 3.00 times, respectively, compared with normal-glucose treatment (P , 0.05).…”
Section: High Glucose Increased Hdac1 and Hdac5 Expression In Schwannmentioning
confidence: 60%